Identification of vacuolar phosphate influx transporters in Brassica napus. (1st September 2022) - Han, Bei; Wang, Chuang; Wu, Tao; Yan, Junjun; Jiang, Aosheng; Liu, Yu; Luo, Yu; Cai, Hongmei; Ding, Guangda; Dong, Xu; White, Philip J.; Xu, Fangsen; et al.
Abstract: Recent progress has shown that vacuolar Pi transporters (VPTs) are important for cellular Pi homoeostasis in Arabidopsis thaliana and Oryza sativa under fluctuating external Pi supply, but the identity and involvement of VPTs in cellular Pi homoeostasis in Brassica napus is poorly understood. Here, we identified two vacuolar Pi influx transporters B. napus, BnA09PHT5;1b and BnCnPHT5;1b, and uncovered their necessity for cellular Pi homoeostasis through functional analysis. Both Brassica proteins are homologs of Arabidopsis AtPHT5;1 with a similar sequence, structure, tonoplast localization, and VPT activity. Brassica pht5;1b double mutants had smaller shoots and larger shoot cellular Pi concentrations than wild‐type B. napus, which contrasts with a previous study of the Arabidopsis pht5;1 mutant, suggesting that PHT5;1‐VPTs play different roles in cellular Pi homoeostasis in seedlings of B. napus and A. thalian a. Disruption of BnPHT5;1b genes also caused Pi toxicity in floral organs, reduced seed yield and impacted seed traits, consistent with the proposed role of AtPHT5;1 in floral Pi homoeostasis in Arabidopsis . Taken together, our studies identified two vacuolar Pi influx transporters in B. napus and revealed the distinct and conserved roles of BnPHT5;1bs in cellular Pi homoeostasis in this plant species. Summary Statement: This study identified two vacuolar Pi influx transporters in Brassica napus, BnA09PHT5;1b and BnCnPHT5;1b, and revealed the important roles of BnPHT5;1bs in cellular Pi homeostasis in this plant species.